2020
DOI: 10.1038/s41598-020-62809-y
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Bacillus subtilis on corrosion behavior of 10MnNiCrCu steel in marine environment

Abstract: Bacillus widely exists in wet natural environment such as soil, water and air, and is often studied as one of representative microorganisms for microbiologically influenced corrosion(MIC) research. In this paper, the growth curve of Bacillus subtilis isolated from marine environment was determined by turbidimetry and its effect on corrosion behavior of 10MnNiCrCu steel was studied by open circuit potential, AC impedance, polarization curve and scanning electron microscopy(SEM). The results showed that with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 22 publications
1
6
0
Order By: Relevance
“…Corrosion reduction results were also obtained with the B. subtilis C2 strain after a period of initial corrosion (Wang et al 2020). Other studies conducted with the genera Bacillus and Pseudomonas showed similar results (Xu et al 2017; Li et al 2019).…”
Section: Discussionsupporting
confidence: 64%
“…Corrosion reduction results were also obtained with the B. subtilis C2 strain after a period of initial corrosion (Wang et al 2020). Other studies conducted with the genera Bacillus and Pseudomonas showed similar results (Xu et al 2017; Li et al 2019).…”
Section: Discussionsupporting
confidence: 64%
“…These processes were accompanied by releasing AgNPs from the hydrogen bonding compartments that may have existed on the surface of ACNPs. The bacteria-killing mechanism due to AgNPs itself has already been explained in detail by references [12,15,16,[54][55][56].…”
Section: Antibacterial Activity Testmentioning
confidence: 99%
“…On the other hand, it has been also widely known that both pathogenic bacteria of Bacillus subtilis (B. subtilis), and Escherichia coli (E. coli) as the representatives of Gram-positive and Gram-negative bacteria, respectively, are commonly present ubiquitously in various natural environment bodies such as soil, wastewater, and air [12,13]. Due to these media frequently being in contact with humans, the bacteria can reach the human body and subsequently generate many infectious and various diseases.…”
Section: Introductionmentioning
confidence: 99%
“…These scientists further reported that corrosions promoted by sulphate-reducing bacteria are 3.5 folds higher than those caused by natural metal oxidation. Acidic compounds (Wang et al 2020) produced by bacteria or bacteria-facilitated extracellular electron transfer (Kato 2016) have been well-documented as the main cause of metal corrosion. Kato (2016) further elaborated on three mechanisms by which microbial extracellular electron transfer (EET) occurs, and these are summarized in Figure 1.…”
Section: Introductionmentioning
confidence: 99%